COMPLAINING IN EFL LEARNERS: DIFFERENCES OF REALIZATIONS BETWEEN MEN AND WOMEN (A CASE STUDY OF INDONESIAN EFL LEARNERS AT THE ENGLISH DEPARTMENT OF THE INDONESIAN UNIVERSITY OF EDUCATION) - Dyah Ayu T.; Didi Sukyadi (Master Program in Linguistics, Diponegoro University, 2011)
In the society, various studies suggest that the way men and women speak is different. Women are considered to be more polite than men and many assumptions arise to support this idea. By looking at that phenomenon, the reseacher attempts to establish evidences and verification about women’s linguistic behavior in which women are theoretically more polite than men are and to discover more information about the characteristics of men and women by investigating the linguistic features between men and women’s speech act, especially in speech act of complaining. The present study investigates the differences of complaining realizations between Indonesian EFL men and women learners. The subjects were selected from the English Department of the Indonesian University of Education, involving 20 advanced male and female students. Data were collected through an open-ended questionnaire in the form of a Discourse Completion Task and a semi-structured interview. The responses were analyzed based on Trosborg’s (1994) complaint strategies as the main analyzer and Rinnert and Nogami’s (2006) taxonomy of the speech act as a supporting device. The study reveals that there is a difference between men and women in proposing the complaining speech act. The findings revealed that men were the highest users of Direct Accusations while women used Indirect Accusations the most. This present study also found that the use of complaining strategies was more frequently employed by women than by men. Gender as the main focus of this research has been proven to have an influence on the choice of complaining strategies: how the gender of a complainer and a complainee plays a role in deciding the strategy of complaining act. This research has supported previous studies on the subject and contributed to the establishment of the knowledge structures of pragmatics, sociolinguistics, cross cultural understanding and English linguistics in general